Produksi uredospora phakopsora pachyrhizi Syd pada tanaman kedelai =Uredospore Production of Phakopsora pachyrbizi Syd. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
Influence of cultivar and growth of soybean to uredospore production of Phakopsora pachyrhizi were under studies. Three soybean cultivars, i.e. Ringgit, Orba, and No. 29, representing susceptible, moderately resistant, and resistant cultivar to soybean rust were inoculated with P.pachyrhizi uredospores at the vegetative, flowering, and pod setting stage. The inoculated plants then were kept under plastic house condition. The resistant cultivar could decrease uredospores production and was effective in decreasing inoculum of P.pachyrhizi. The more resistant the soybean cultivars, the less uredia formed, the less mature uredia, and the less production of uredospores. Soybean plants inoculated at the flowering stage was more suitable for the increment of uredospore production compared with that inoculated at the vegetative or pod setting stages.